The Impact of Work Posture on Knee Functionality in Young Farmers: A Study in Pancasari Village - Dewi, Gusti Ayu Komang Anita Triana; Wibawa, Ari; Wahyuni, Nila (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : Farming activities require intensive body use and often involve work postures that can affect knee functional health. This study aims to determine whether there is a relationship between work posture and knee functional ability in farmers in Pancasari Village. Methods : This research employed an observational analytic method with a cross-sectional approach involving 64 farmers aged 25-35 years in Pancasari Village. The sampling technique used was purposive sampling. The independent variable measured was the farmers' work posture using the Ovako Work Posture Analysis System (OWAS). The dependent variable measured was knee functional ability using the Knee Injury and Osteoarthritis Outcome Score questionnaire. Results : The non-parametric Spearman's rho analysis showed a p-value of 0.000 (p < 0.05) and a correlation coefficient of r = -0.641, indicating a significant negative relationship between work posture and knee functional ability. Conclusion : There is a significant negative relationship between work posture and knee functional ability in farmers aged 25-35 years in Pancasari Village. These findings indicate the need for interventions to improve work posture to prevent a decline in knee function.   Keywords : Work posture, Knee functional ability, Farmers, OWAS (Ovako Work Posture Analysis System), Knee Injury and Osteoarthritis Outcome Score (KOOS)